CALLED—PROVED—OBEDIENT: A STUDY IN THE BAPTISM AND TEMPTATION NARRATIVES OF MATTHEW AND LUKE - Thompson, George Harry Packwood (The journal of theological studies, 1960)
G. H. P. THOMPSON; CALLED—PROVED—OBEDIENT: A STUDY IN THE BAPTISM AND TEMPTATION NARRATIVES OF MATTHEW AND LUKE, The Journal of Theological Studies, Volume XI,